2018
DOI: 10.1051/e3sconf/20184400065
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the impact of electric vehicles on the power grid

Abstract: Abstract. The paper presents problems related to the impact of electric vehicles connected to the power grid on energy parameters. Basic methods of control in power grids were discussed and results of the simulation were presented with regards to the power distribution, voltage drops and losses in the transmission lines. The simulation was conducted based on the example of CIGRE 11, to which electric vehicle charging stations were connected in several selected points, with the possibility of energy release int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Cheng et al found that large-scale use of battery electric vehicles (BEVs) could actually provide benefits in terms of CO 2 emission reductions at grid level [29]. In addition, Kasprzyk et al present results according to which the use of BEVs can reduce energy losses by modifying the shape of the curve for daily load [30].…”
Section: Introductionmentioning
confidence: 99%
“…Cheng et al found that large-scale use of battery electric vehicles (BEVs) could actually provide benefits in terms of CO 2 emission reductions at grid level [29]. In addition, Kasprzyk et al present results according to which the use of BEVs can reduce energy losses by modifying the shape of the curve for daily load [30].…”
Section: Introductionmentioning
confidence: 99%